2020
DOI: 10.1101/2020.08.30.274001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct effects of different matrix proteoglycans on collagen fibrillogenesis and cell-mediated collagen reorganization

Abstract: The extracellular matrix (ECM) is a complex mixture composed of fibrillar collagens as well as additional protein and carbohydrate components. Proteoglycans (PGs) contribute to the heterogeneity of the ECM and play an important role in its structure and function. While the small leucine rich proteoglycans (SLRPs), including decorin and lumican, have been studied extensively as mediators of collagen fibrillogenesis and organization, the function of large matrix PGs in collagen matrices is less well known. In th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…However, in native ECM, the content of free GAGs and PG-bound GAGs is still unclear. As different PGs appear to interact differently with collagen 29 , PG-bound GAGs (fixed charge residues) might have complicated effects on mechanical communication between cells. Thus, there is a particular need to investigate and compare the regulation of free versus PG-bound GAGs on fibrous network as one future direction for modeling force transmission in native ECM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in native ECM, the content of free GAGs and PG-bound GAGs is still unclear. As different PGs appear to interact differently with collagen 29 , PG-bound GAGs (fixed charge residues) might have complicated effects on mechanical communication between cells. Thus, there is a particular need to investigate and compare the regulation of free versus PG-bound GAGs on fibrous network as one future direction for modeling force transmission in native ECM.…”
Section: Discussionmentioning
confidence: 99%
“…All the samples were sealed with parafilm and kept in PBS at 4°C. Second-harmonic generation (SHG) imaging was used to visualize collagen fibers 29 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous in vitro studies have demonstrated that the high‐molecular‐weight of chondroitin sulfate retards the rate of collagen fibril formation by monitoring gelation rate 50 . In contrast, recent studies have shown that versican, but not aggrecan, promotes collagen fibrillogenesis in a turbidity assay, and chondroitin sulfate gives a minor supportive effect on this stimulation 6 . These in vitro studies suggest a complexity of interaction between collagen fibrils and specific proteoglycan core proteins and GAGs in the regulation of collagen fibril formation.…”
Section: Discussionmentioning
confidence: 99%
“…Proteoglycans such as aggrecan and versican, with sulfated glycosaminoglycan (GAG) chains can form big aggregates, retain water, and provide the ability to resist compressive and tensile force to the tendon 2,3 . Proteoglycans may also affect collagen fibrllogenesis 6,7 . Thus both collagen fibers and proteoglycans are important modulators of mechanical properties of tendons.…”
Section: Introductionmentioning
confidence: 99%
“…This bottom-up approach relies on stromal cell ECM contraction and physical interactions with the matrix to form high cell density tissue mimics (3,45). Although we have learned a great deal from current microtissue systems, there is a need for systems where the matrix can be tuned to better understand the contribution of ECM properties to tissue morphogenesis (45) and ECM-based diseases such as fibrosis (46). Currently, most commercially available ECM systems (e.g., type I collagen, fibrin, Matrigel) have limited control over biochemical and biophysical properties and would benefit from synthetic versions where such properties can be modulated.…”
Section: Microtissues Via Contractile Fibrous Hydrogel Assembliesmentioning
confidence: 99%